The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1472-6807-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of alkyl hydroperoxidase D like protein PA0269 from Pseudomonas aeruginosa: Homology of the AhpD-like structural family

Abstract: BackgroundAlkyl hydroperoxidase activity provides an important antioxidant defense for bacterial cells. The catalytic mechanism requires two peroxidases, AhpC and AhpD, where AhpD plays the role of an essential adaptor protein.ResultsThe crystal structure of a putative AhpD from Pseudomonas aeruginosa has been determined at 1.9 Å. The protein has an all-helical fold with a chain topology similar to a known AhpD from Mycobacterium tuberculosis despite a low overall sequence identity of 9%. A conserved two α-hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
4
31
0
Order By: Relevance
“…Despite barely conserved primary sequences ( Supplementary Fig. 5b), we noted that 109-139 amino acids of the Sesn-A domain show a very distant sequence homology to YP_296737.1 as well as to AhpD, a well-characterized alkylhydroperoxidase in Mycobacterium tuberculosis [21][22][23] , as formerly reported 2 . The homology region corresponds to the helix-turn-helix motif of AhpD, a signature motif found in the family of AhpD-like oxidoreductases [21][22][23] .…”
Section: Yp_2967371 (supporting
confidence: 69%
See 3 more Smart Citations
“…Despite barely conserved primary sequences ( Supplementary Fig. 5b), we noted that 109-139 amino acids of the Sesn-A domain show a very distant sequence homology to YP_296737.1 as well as to AhpD, a well-characterized alkylhydroperoxidase in Mycobacterium tuberculosis [21][22][23] , as formerly reported 2 . The homology region corresponds to the helix-turn-helix motif of AhpD, a signature motif found in the family of AhpD-like oxidoreductases [21][22][23] .…”
Section: Yp_2967371 (supporting
confidence: 69%
“…5b), we noted that 109-139 amino acids of the Sesn-A domain show a very distant sequence homology to YP_296737.1 as well as to AhpD, a well-characterized alkylhydroperoxidase in Mycobacterium tuberculosis [21][22][23] , as formerly reported 2 . The homology region corresponds to the helix-turn-helix motif of AhpD, a signature motif found in the family of AhpD-like oxidoreductases [21][22][23] . The relative position of the motif within the primary sequence is similar between hSesn2 and YP_296737.1 but different in AhpD ( Supplementary Fig.…”
Section: Yp_2967371 (supporting
confidence: 67%
See 2 more Smart Citations
“…The main strategy employed is the production of enzymes that degrade ROS species to maintain stress levels within a range of tolerance [91]. Our bacteria expressed alkyl hydroperoxidase D ( ahpD ) and alkyl hydroperoxide reductase C ( ahpC ), which provide significant antioxidant protection and have been described in various bacteria [92–94]. Additionally, Chung et al [95] demonstrated that deletion of the ahpC genes alone in V .…”
Section: Discussionmentioning
confidence: 99%